2014
DOI: 10.4236/health.2014.618279
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nosocomial Infections in Selected Teaching Hospitals, Qazvin, Iran

Abstract: Introduction: Hospital infections prolong patient hospitalization, necessitate additional treatment, increase mortality rate, raise hospital expenses, and even reduce the level of health in the society. The purpose of this research was to study hospital infections in selected hospitals of Qazvin. Methods and Materials: This was an analytic-cross-sectional study. The research population consisted of 25,628 hospitalized patients in the first eight months of 2012 in three selected hospitals of the Qazvin Province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The studies of Brinsley et al (2005) who associated perceived susceptibility and severity with behaviors contributing to antimicrobial resistance, Lewis and Thompson (2009) who associated perceived susceptibility with infection control, and Boyer (2008) who associated self-efficacy with adult obesity management provide reinforce the usefulness of this model. More in-depth research is needed to explore provider behavior, including school nurses, which may result in improved patient outcomes.…”
Section: Recommendations For Future Researchmentioning
confidence: 79%
See 1 more Smart Citation
“…The studies of Brinsley et al (2005) who associated perceived susceptibility and severity with behaviors contributing to antimicrobial resistance, Lewis and Thompson (2009) who associated perceived susceptibility with infection control, and Boyer (2008) who associated self-efficacy with adult obesity management provide reinforce the usefulness of this model. More in-depth research is needed to explore provider behavior, including school nurses, which may result in improved patient outcomes.…”
Section: Recommendations For Future Researchmentioning
confidence: 79%
“…Focus groups revealed that physicians in the study had low perceived susceptibility, as they did not feel antimicrobial resistance was a problem in their institutions, and had low perceived severity as they ranked several other health care issues in their hospitals as more challenging than antimicrobial resistance. Lewis and Thompson (2009) used the HBM to understand lack of compliance with infection control practices of health care providers. Perceived susceptibility was found to be the most influential variable.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…4 Farzianpour et al also identified that the majority of HAIs in their study in three teaching hospitals in Qazvin Province, Iran, developed among ICU patients. 7 Salamati et al found that the highest proportion of paediatric HAIs occurred in the NICU (40%), followed by the neonatal surgery ward (35%) and the neonatal ward (25%). 12 The low rate of HAIs observed in this study could be due to good infection control practices with continuous surveillance, and the health education program provided for the hospital staff.…”
Section: Hais In Iranmentioning
confidence: 99%
“…Farzianpour et al identified pneumonia and UTIs as their most common HAIs. 7 Ding et al reported that lower respiratory tract infections accounted for most of the infections (68.4%) in their ICU, followed by UTIs (15.9%), bloodstream infection (5.9%), and gastrointestinal tract infection (2.5%). 3 Hajibagheri et al determined that 30 to 50% of HAIs were pneumonia related to mechanical ventilation in the ICU of Tohid Hospital in Sanandaj, Iran.…”
Section: Hais In Iranmentioning
confidence: 99%
See 1 more Smart Citation